A pilot survey on perceptions and knowledge of generic medicines among consumers in Penang, Malaysia - Al-Gedadi NA; Hassali MA; Shafie AA (Centro de Investigaciones y Publicaciones Farmaceuticas, 2008)
Objective: To explore the consumers' perceptions and knowledge towards issues surrounding generic medicines utilization in Penang, Malaysia.Methods: A cross sectional survey was conducted with consumers who attended the annual University open day. Using convenience sampling, survey forms were distributed to the respective consumers via the help of a group of trained 1st year pharmacy students. For a period of 5 days, 400 respondents had participated in the survey. Analysis of the response from the collected forms yielded in 396 usable forms.Results: Only 28.3% (n=112) of the respondents were familiar with the term "generic medicines". More than 70% of the respondents do not know that generic medicines can be marketed under different names. About 34% (n=38) of consumers stated that they had been given information regarding generics by their pharmacists. In terms of side effects, about 32% (n=127) of the respondents felt that generic medicines may cause more side effects than branded medicines. Majority of the consumers surveyed (64%) understand that generic cost less compared to their branded counterparts.Conclusion: This survey showed that there is a gap in consumers' knowledge and understanding about generic medicines. The findings also suggest that direct patient education by the healthcare providers on issues relating to safety and efficacy of generic medicines could further enhance their uptake.